2015
DOI: 10.1371/journal.pone.0128787
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intrinsic Connectivity of the Default Mode Network in Temporal Lobe Epilepsy: Evidence from Resting-State MEG Recordings

Abstract: The electrophysiological signature of resting state oscillatory functional connectivity within the default mode network (DMN) during spike-free periods in temporal lobe epilepsy (TLE) remains unclear. Using magnetoencephalographic (MEG) recordings, this study investigated how the connectivity within the DMN was altered in TLE, and we examined the effect of lateralized TLE on functional connectivity. Sixteen medically intractable TLE patients and 22 controls participated in this study. Whole-scalp 306-channel M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 97 publications
3
50
0
Order By: Relevance
“…Another study using simultaneous EEG and functional MRI found that AEDs resistance and uncontrolled seizures are associated with a greater reduction in DMN connectivity than epilepsy alone, which suggests the alteration of DMN might be useful as a biomarker for treatment resistance [23]. In addition, another previous study using resting state functional MRI also suggested that the connectivity within the DMN is reinforced during spike-free periods [24]. All of these previous reports, in line with our present findings, suggest the alterations of DMN regions in patients with GGE.…”
Section: Discussionmentioning
confidence: 97%
“…Another study using simultaneous EEG and functional MRI found that AEDs resistance and uncontrolled seizures are associated with a greater reduction in DMN connectivity than epilepsy alone, which suggests the alteration of DMN might be useful as a biomarker for treatment resistance [23]. In addition, another previous study using resting state functional MRI also suggested that the connectivity within the DMN is reinforced during spike-free periods [24]. All of these previous reports, in line with our present findings, suggest the alterations of DMN regions in patients with GGE.…”
Section: Discussionmentioning
confidence: 97%
“…However, IC is still a widely used technique for revealing altered FC and has been applied in cases of brain tumors [56], brain lesions [57], and other disorders. In addition, in source-level network analyses, the IC has been suggested to effectively represent the true coupling of two brain regions with a nonzero time delay using MEG data [31,58]. Thus, we used the IC method to calculate the FC matrix for each subject in the source space.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that asymmetric and slow activity of the delta band (1-4 Hz) can reliably lateralize to the epileptogenic hemisphere [14,[60][61][62]. Indeed, significant differences in delta band activity were found between TLE patients and controls in network analyses [31,63,64]. Thus, we only selected one frequency band, the delta band, as our frequency band of interest.…”
Section: Complexitymentioning
confidence: 99%
See 2 more Smart Citations